Bond Strength Behavior in Rubberized Concrete - Al-Quraishi, Hussein; Khudhayer Najim Abdullah Kammash; Zinah Asaad Abdul-Husain (International Journal of Sustainable Construction Engineering and Technology, 2022)
Through an experimental program of eighteen specimens presented in this paper, the bond strength between reinforcing bar and rubberized concrete that produced from adding waste tire rubber instead of natural aggregate. The fine and coarse aggregate were replaced in 0%, 25%, and 50% with the small piece of waste tire. Natural aggregate replacement ratio, rebar size, embedded length of rebar, yield stress of rebar, cover of concrete and concrete compressive strength were the parameters studied in this investigation. Ultimate bond stress, bond stress-slip response and failure modes were presented. The experimental results reported that a reduction of 19% in bond strength was noticed in rubberized concrete compared with conventional concrete. The bond strength of rubberized concrete increased when the concrete cover, compressive strength of concrete and yield stress of rebar were increased. Meanwhile, increase embedded length of rebar and rebar size decreases the bond strength. The push-out and splitting failure were the failure modes observed in rubberized concrete.